Jesus’ Hour In the Fourth Gospel: A Reading of John 12: 20-36. (Hekima Review, 2005)
The “Hour of Jesus” is one of the most significant themes in the fourth gospel. It is spoken of from the beginning of John’sgospel, but it will reach its higher point in chapter 12 with the arrival of the Greeks, which marks the coming of the hour. We first come across it in chapter 2:4 where Jesus, responding to his mother’s request to provide wine for the party, points out the fact that the hour has not yet come: “O woman, what have you to do with me? My hour has not yet come.”